Andersonville: A Story of Rebel Military Prisons - McElroy, John, 1846-1929 (Salt Lake City, UT : Project Gutenberg, 2004)
"Andersonville: A Story of Rebel Military Prisons" by John McElroy is a historical account written in the late 19th century that recounts the experiences of a Union soldier captured during the Civil War. This narrative offers a poignant look into the horrors and conditions of Confederate military prisons, particularly focusing on Andersonville, where thousands of Union soldiers endured severe hardship, starvation, and cruelty. McElroy, who was a soldier himself, draws from personal experience, lending authenticity to his vivid descriptions of suffering and resilience. The opening of the book establishes the setting and context before diving into McElroy's harrowing experiences. He introduces his situation as a prisoner, highlighting the tremendous challenges faced by the captured soldiers. The narrative paints a stark picture of the landscapes, battles, and the psychological and physical toll suffered by the author and his comrades. McElroy$1 (Bs writing reflects both a deep-seated anger toward the injustices inflicted by the Confederate forces and a profound dedication to ensuring that the sacrifices of those who endured such torment would not be forgotten. As the story unfolds, readers can expect a mixture of dire reality, personal anecdotes, and critical reflections on the broader implications of war and its moral consequences. (This is an automatically generated summary.)s
Release date is 2004-06-01
David Widger
Keywords: Andersonville Prison; Confederate States of America. Army -- Prisons; Military prisons; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons